But what if we're wrong? : thinking about the present as if it were the past - Klosterman, Chuck, 1972- (Blue Rider Press, 2016)
Klosterman "visualizes the contemporary world as it will appear to those who'll perceive it as the distant past, [asking] questions that are profound in their simplicity: How certain are we about our understanding of gravity? How certain are we about our understanding of time? What will be the defining memory of rock music, five hundred years from today? How seriously should we view the content of our dreams? How seriously should we view the content of television? Are all sports destined for extinction?"--Amazon.com.